Early Dendritic Dystrophy in Human Brains With Primary Age-Related Tauopathy - Shi, Yan-Bin; Tu, Tian; Jiang, Juan; Zhang, Qi-Lei; Ai, Jia-Qi; Pan, Aihua; Manavis, Jim; Tu, Ewen; Yan, Xiao-Xin (Frontiers in Aging Neuroscience, 2020)
Dystrophic neurites (DNs) are found in many neurological conditions such as traumatic brain injury and age-related neurodegenerative diseases. In Alzheimer’s disease (AD) specifically, senile plaques containing silver-stained DNs were already described in the original literature defining this disease. These DNs could be both axonal and dendritic in origin, while axonal dystrophy relative to plaque formation has been more extensively studied. Here we demonstrate an early occurrence of dendritic dystrophy in the hippocampal CA1 and subicular regions in human brains (n=23) with primary age-related tauopathy (PART), with neurofibrillary tangle (NFT) burden ranged from Braak stages I to III in the absence of cerebral β-amyloid (Aβ) deposition. In Bielschowsky’s silver stain, segmented fusiform swellings on the apical dendrites of hippocampal and subicular pyramidal neurons were observed in all the cases, primarily over the stratum radiatum. The numbers of silver-stained neuronal somata and dendritic swellings counted over CA1 to subiculum were positively correlated among the cases. Swollen dendritic processes were also detected in sections immunolabeled for phosphorylated tau (pTau) and sortilin. In aged and AD brains with both Aβ and pTau pathologies, silver and immunolabeled dystrophic-like dendritic profiles occurred around and within individual neuritic plaques. These findings implicate that dendritic dystrophy can occur among hippocampal pyramidal neurons in human brains with PART. Therefore, as with the case of axonal dystrophy reported in literature, dendritic dystrophy can develop prior to Alzheimer-type plaque and tangle formation in the human brain.